Complete angiographic obliteration of intracranial AVMs with endovascular embolization: incomplete embolic nidal opacification is associated with AVM recurrence. (15th June 2010) - Reig, Adam S; Rajaram, Ravi; Simon, Scott; Mericle, Robert A
Abstract : Background: Embolization of intracranial arteriovenous malformations (AVMs) is generally a preoperative adjunctive procedure in the USA. However, sometimes embolization can result in complete angiographic obliteration of the AVM. There is significant controversy regarding the best management strategy for this subset of patients. There is a scarcity of literature predicting which embolized, angiographically obliterated AVMs are likely to recur and which ones are cured. We present our series of patients with complete obliteration of their AVMs from embolization. Methods: A prospectively maintained database identified 122 patients who underwent embolization of an intracerebral pial AVM with liquid embolics. Eighteen patients (15%) achieved complete angiographic obliteration of the AVM with embolization. We followed several parameters to assess possible predictors of recurrence. Results: Fifteen of 18 patients (83%) had angiographic/anatomical follow-up to assess for AVM recurrence and 3 (17%) refused angiographic follow-up. Three patients underwent surgical resection with intraoperative angiography despite complete AVM obliteration with embolization alone. Thirteen of the 15 (87%) patients with follow-up remained obliterated at time of follow-up, and all of these patients had an embolic cast that had a similar morphology to the AVM nidus. Two of 15 patients (13%) had AVM recurrence, both of whom had incomplete embolic nidal opacification (proximal pedicle embolization). Conclusions: A minority of intracranial AVMs can be safely obliterated with stand-alone embolization. Proximal occlusion of feeding arteries appears to be associated with recurrence. Prospective studies with longer follow-up and larger patient numbers are necessary.